PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DENGAN ETIKA KOMITMEN DIREKSI SEBAGAI VARIABEL MODERASI - Nofrianto, Mohamad Yusuf; Azizah, Nurna; Usman, Darman (UNIB Press, 2020)
This study aims to examine the causal relationship between corporate governance mechanism variables, board of directors commitment ethics, and company performance. Corporate governance is measured by looking at the effectiveness of commissioners and audit committees, ethical commitment of the board of directors is measured score of 0 to 4 and company performance is measured by return on assets (ROA) and return on equity (ROE). This study found that corporate governance have an influence on company performance as measured using return on assets (ROA), while corporate governance have no influence on company performance as measured using return on assets (ROE). The ethical commitment of the board of directors is unable to strengthen the relationship between corporate governance and company performance as measured by ROA or ROE.